A processing method for electrode material and a processing method for electrode pole piece

By performing medium-speed, high-speed and low-speed stirring in the granulator, the loose density of powder is controlled, and the problems of complex and cost of preparing dry electrode sheets in the existing dry method are solved, and the uniformity of the electrode material is achieved. Improvement of electrochemical performance.

CN116173828BActive Publication Date: 2025-02-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310152550.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-02-11
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The existing dry method has complex processes, difficult operation, long preparation cycles, high heating energy consumption, resulting in high preparation costs.

Method used

The process of electrode materials is carried out by using a granulator. Through the steps of medium-speed stirring, high-speed stirring and low-speed dispersion, the loose density of the powder is controlled, and the material mixing, fibrosis and dispersion are achieved, and the particles have good mixing effect are prepared. Electrode material with uniform diameter.

Benefits of technology

The processing process of electrode materials is simplified, the uniformity and electrochemical properties of the materials are improved, the preparation cost is reduced, and the problem of uneven holes and edges on the electrode film is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173828B_ABST
    Figure CN116173828B_ABST
Patent Text Reader

Abstract

The present invention discloses a processing method of an electrode material and a processing method of an electrode pole piece, and belongs to the technical field of lithium-ion battery materials. In the processing of the electrode material, the material is stirred and mixed by a granulator, and the change of the loose density of the material during the stirring process is monitored, so that the uniformity of the material mixing can be regulated, and the heat generated by the granulator during the high-speed stirring process is used to regulate the fiberization degree of the binder; at the same time, the electrode material prepared by the granulator has a good mixing effect and uniform particle size. When the powder is rolled into a film, the thickness of the prepared film is uniform and the consistency is good, which solves the problems of holes or uneven edges on the electrode film. The secondary battery prepared by this method improves the manufacturing efficiency and electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery materials, and in particular to a method for processing an electrode material and a method for processing an electrode pole piece. Background Art

[0002] In recent years, with the rapid growth of lithium-ion battery applications in electric vehicles, energy storage, 3C and other fields, the overall output and market size of lithium-ion batteries in the world have increased rapidly. However, affected by the epidemic and the rise in prices of some raw materials, the cost reduction measures in the industry when preparing batteries are mainly to select low-cost materials, develop new processes, and improve product qualification rates. For example: choosing low-cost electrode materials, separators and electrolytes, this method will lead to poor battery safety. Another example: increasing the coating surface density to achieve the purpose of reducing battery costs, but there will be problems of coating leakage and inability to dry in the oven during the coating process, so the coating surface density cannot be increased indefinitely, resulting in a limit on the coating surface density. Another example: using a dry process to prepare dry electrode pole pieces, this process reduces the coating and pole piece baking steps in the preparation process, eliminates the use of toxic solvent NMP, and the raw materials are stirred, dispersed and rolled into a film, and then the membrane and the current collector are composited to obtain the electrode sheet. It has the advantages of high degree of automation, good product quality stability, and low loss of personnel, materials and energy.

[0003] CN112687833A discloses a method for preparing a dry electrode sheet, which includes: mixing raw material powders, heating and fiberizing to obtain sheet powder, vertically rolling and horizontally rolling the sheet powder to obtain a membrane, and the membrane and foil enter the laminating roller together to obtain the electrode sheet by roller molding. CN114583111A discloses a method for preparing a continuous discharge dry electrode, which includes the following steps: feeding the positive electrode material or the negative electrode material into a powder metering tank; mixing through a mixing barrel; high-temperature stirring and shear mixing through four cavities; conveying and discharging through three chambers; crushing the agglomerated part inside through an ultrasonic vibration screen; pressing and rolling; cutting. CN114171710A discloses an in-situ preparation method for a dry electrode membrane, comprising the following steps: under a dew point of -25-65°C, premixing active material dry powder, polymer binder dry powder and conductive agent dry powder, placing the mixture in a twin-screw extruder through radiation heating to cause an in-situ cross-linking reaction of the mixture, and extruding to form a dry electrode membrane; wherein the binder is a low melting point adhesive of 50-120°C.

[0004] In the above-mentioned dry preparation methods of dry electrode sheets, some are to heat the raw material powders after mixing to make them fiberized, some are to stir and shear mix at high temperature, and some are to crosslink the mixture in situ by radiation heating in a twin-screw extruder. This preparation process is relatively complicated, difficult to operate, has a long preparation cycle, and has heating energy consumption. Therefore, there is also the problem of high preparation cost.

[0005] In view of this, it is necessary to provide a method for processing electrode materials and a method for processing electrode plates. Summary of the invention

[0006] The purpose of the present invention is to provide a method for processing an electrode material and a method for processing an electrode pole piece in order to overcome the defects of the above-mentioned prior art.

[0007] The present invention solves the technical problem by adopting the following technical solutions.

[0008] An embodiment of the present invention provides a method for processing an electrode material, comprising the following steps:

[0009] Step 1: Add the electrode active material and the conductive agent into a granulator, and stir at a medium speed of 1000-2000 rpm for 5-15 minutes to obtain a uniform mixture, and test the bulk density of the mixture to be BD0;

[0010] Step 2: Add a binder to the above mixture and stir at a high speed of 5000-7000 rpm for 3-10 min to obtain a fiberized material. The bulk density BD of the fiberized material at a stirring time of t is required to be tested. t , among which, BD t <BD0, and 20%<BD t / BD0<50%;

[0011] Step 3: The fibrous material is then dispersed at a low speed of 100-500 rpm for 5-10 minutes to obtain an electrode material with uniform particles.

[0012] The present invention provides a method for processing an electrode plate, which comprises: rolling an electrode material into a dry film sheet, then rolling the dry film sheet into a roll, and then laminating the dry film sheet on both sides of a current collector by flat-plate hot pressing to obtain a dry electrode plate, wherein the electrode material is obtained by processing according to the above-mentioned processing method.

[0013] The present invention provides a lithium ion battery, which comprises the above-mentioned electrode plate.

[0014] The present invention has the following beneficial effects:

[0015] The present invention provides a method for processing an electrode material and a method for processing an electrode plate. By controlling the stirring speed of a granulator, the material mixing, material fiberization and material breaking-up can be achieved in the granulator. The material mixing uniformity can be regulated by monitoring the change in the loose density of the material during fiberization, thereby preparing an electrode material with good mixing effect and uniform particle size. When the electrode material is calendered into a film, the thickness of the prepared film is uniform and the consistency is good, which solves the problems of holes or uneven edges on the electrode film. The secondary battery prepared by the method improves the manufacturing efficiency and electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is a schematic diagram of the dry electrode powder fiberization processing method;

[0018] Figure 2 is a schematic diagram of a granulator;

[0019] Figure 3 The loose packed density of the powder in Example 1 varies with the stirring time;

[0020] Figure 4 This is a photo of the powder after high-speed stirring in Example 1;

[0021] Figure 5 This is a photo of the powder after being dispersed at a low speed in Example 1;

[0022] Figure 6 This is the SEM image of the electrode prepared in Example 1. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0024] The dry electrode powder fiberization processing method provided in the embodiment of the present invention is used to solve the problems in the prior art that the uniformity of powder mixing cannot be monitored, an additional heating process is used for the powder, the uneven powder particle size causes uneven discharge, the prepared electrode sheets have poor uniformity, holes, broken strips or uneven edges, and the preparation process is complicated, the operation is difficult, and the heating energy consumption is high.

[0025] The following is a detailed description of a method for processing an electrode material and a method for processing an electrode plate provided in an embodiment of the present invention.

[0026] In a first aspect, an embodiment of the present invention provides a method for processing an electrode material, comprising the following steps:

[0027] Step 1: Add the electrode active material and the conductive agent into the granulator, and stir at a medium speed of 1000-2000 rpm for 5-15 minutes, control the powder temperature to 25°C-50°C, obtain a uniform mixture, and test the bulk density of the mixture to be BD0;

[0028] Step 2: Add the binder to the above mixture, and stir at a high speed of 5000-7000rpm for 3-10min, and control the powder temperature to 70℃-160℃ to obtain a fiberized material. The bulk density BD of the fiberized material at the stirring time t is required to be tested. t , among which, BD t <BD0, and 20%<BD t / BD0<50%;

[0029] Step 3: Use a low speed of 100-500 rpm to break up the fiberized material, the low speed stirring time is 5-10 minutes, and the powder temperature is controlled at 25°C-35°C to obtain a uniformly granulated electrode material, wherein the particle size of the electrode material is 0.2-5 mm.

[0030] A processing method for an electrode material of the present embodiment can achieve material mixing, material fiberization and material dispersion in a granulator by controlling the stirring speed of the granulator, and can control the uniformity of material mixing by monitoring the change of the loose density of the material during the fiberization of the material, thereby preparing an electrode material with good mixing effect and uniform particle size. The electrode material prepared by the above method can be used to produce a membrane with good apparent performance, and the above membrane can be used to produce a lithium battery with good battery performance.

[0031] In an optional embodiment, the test method for the bulk density is a Scott volumeter method or a vibrating funnel method, both of which are existing mature testing methods, suitable for the use site of the granulator, and convenient for monitoring the changes in the bulk density of the fiberized material. Of course, the test method for the bulk density may also be other test methods with the same or similar effects.

[0032] Specifically about the bulk density BD of the fiberized material at stirring time t t , this BD t It can be one or more. For example, the fiberized material can be taken at a stirring time of 3 minutes and its loose density can be tested. For another example, the fiberized material can be taken at a certain time interval, for example, the time interval can be 1 minute, 2 minutes, 3 minutes or 5 minutes and its loose density can be tested. The total number of tests during the mixing process can be 2, 4, 6, 8 or 10 times. By testing and obtaining multiple BD t The curve of loose density changing with stirring time can be obtained by fitting and other methods (see Figure 3 The fiberization degree of the material and the appropriate stirring time at different times can be obtained through the curve, which is convenient for subsequent staff to check the fiberization degree and stirring time of the material.

[0033] In an optional embodiment, the mass ratio of the electrode active material, the conductive agent and the binder is 80-98:1-5:1-10;

[0034] The binder is a fiberizable binder, and the binder includes at least one of polyvinylidene fluoride, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber;

[0035] The conductive agent includes at least one of acetylene black, conductive carbon black, Ketjen black, graphene, carbon nanotubes and carbon fibers, and the bulk density of the conductive agent is 0.05-0.2 g / cm 3 ;

[0036] The electrode active material is a positive electrode material or a negative electrode material. The positive electrode material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganate, lithium cobaltate, lithium titanate and lithium nickel cobalt manganate. The bulk density of the positive electrode material is 1.0-2.0 g / cm 3 The negative electrode material includes at least one of graphite, silicon, silicon oxide, hard carbon and soft carbon, and the bulk density of the negative electrode material is 0.5-1.5g / cm 3 .

[0037] In an optional embodiment, in order to achieve material mixing, material fiberization and material dispersion in the granulator by controlling the stirring speed of the granulator, the granulator includes: 1. an outer cylinder; 2. an inner cylinder; 3. a water flow channel; 4. a cooling water inlet pipe; 5. a cooling water outlet pipe; 6. a stirring shaft; 7. a first rotary drive; 8. a large-blade agitator; 9. a small-blade agitator; 10. a temperature probe; 11. a second rotary drive; and 12. a cover. Among them: an outer cylinder 1, an inner cylinder 2 sleeved in the outer cylinder 1 and a cover 12 covered on the outer cylinder 1, a water flow channel 3 is formed between the outer cylinder 1 and the inner cylinder 2, a water inlet and a water outlet are arranged on the side wall of the outer cylinder 1, the water inlet and the water outlet are both connected to the water flow channel 3, the water inlet is connected to the cooling water inlet pipe 4, and the water outlet is connected to the cooling water outlet pipe 5, wherein the cooling water inlet pipe 4 and the cooling water outlet pipe 5 are both provided with control valves; a stirring shaft 6 is arranged in the inner cylinder 2, and the stirring shaft 6 is driven to rotate by the first rotary driver 7; a large paddle stirrer 8 and a small paddle stirrer 9 are sleeved on the stirring shaft 6, and the small paddle stirrer 9 and the large paddle stirrer 8 are arranged in sequence along the direction close to the bottom of the inner cylinder 2; a temperature probe 10 is arranged in the inner cylinder 2, and the temperature probe 10 is connected to the temperature display located outside the outer cylinder 1, where the temperature in the inner cylinder 2 can be understood in real time through the temperature display, thereby facilitating the regulation of the temperature in the inner cylinder 2 by the cooling water.

[0038] The granulator controls the stirring speed of the stirring shaft 6 through the first rotary driver 7, and further controls the stirring effects of the large-blade stirrer 8 and the small-blade stirrer 9, wherein the width and length of the blades of the large-blade stirrer 8 are both greater than the width and length of the small-blade stirrer 9, and this double-layer blade design has a better stirring effect; in addition, in this embodiment, the blades of the large-blade stirrer 8 have a certain sharpness, and their shape is, for example, arrow-shaped, so that while reducing the speed of fiberization stirring, the fiberization time can also be reduced.

[0039] In addition, the granulator is designed with a water flow channel 3 and a cooling water inlet pipe 4 and a cooling water outlet pipe 5 connected to the water flow channel 3. By controlling the control valve switches on the cooling water inlet pipe 4 and the cooling water outlet pipe 5, it is possible to control whether there is cooling water in the water flow channel 3, and then the temperature of the powder in the inner cylinder 2 can be controlled to meet the temperature requirements of the material at different stages.

[0040] Specifically, in the control of cooling water at different stirring stages, the method for controlling the temperature of the powder in step 1 is: open the control valve on the cooling water inlet pipe and the control valve on the cooling water outlet pipe, so that cooling water is passed into the water flow channel; the method for controlling the temperature of the powder in step 2 is: close the control valve on the cooling water inlet pipe, and keep the control valve on the cooling water outlet pipe in an open state, so that there is no cooling water in the water flow channel; the method for controlling the temperature of the powder in step 3 is: open the control valve on the cooling water inlet pipe, and keep the control valve on the cooling water outlet pipe in an open state, so that cooling water is passed into the water flow channel. The heat generated by the stirring paddle during the stirring process is regulated by controlling the cooling water, so that the material mixing, material fiberization and material breaking are completed in the granulator. In addition, the heat generated by the stirring paddle during high-speed stirring is used to make the binder fiberized while mixing, which is beneficial to the cutting and fiberization effect of the binder. The fiberization effect of the high-speed mixer with this structure is significantly better than that of the ordinary high-speed mixer, and the binder can be fully fiberized.

[0041] In an optional embodiment, in order to facilitate the stirring of the powder and avoid excessive powder in the inner barrel affecting the effect of powder stirring, the amount of powder added to the granulator is 40-70% of the volume of the inner barrel.

[0042] In an optional embodiment, in order to make the mixing efficiency higher and the particle size more uniform, the inner cylinder 2 is driven to rotate by the second rotary driver 11. The rotation direction of the inner cylinder 2 driven by the second rotary driver 11 is opposite to the rotation direction of the stirring shaft 6 driven by the first rotary driver 7. During the mixing process, the inner cylinder 2 rotates clockwise and the stirring shaft 6 rotates counterclockwise, and the powder is broken up and mixed by countercurrent.

[0043] In a second aspect, an embodiment of the present invention provides a method for processing an electrode plate, which comprises: rolling the above-mentioned electrode material into a dry film, rolling it into a roll, and bonding the dry film to both sides of a current collector by flat-plate hot pressing to obtain a dry electrode plate.

[0044] In an optional embodiment, the temperature of the flat plate hot pressing is 80-200°C, preferably 120-180°C.

[0045] When the electrode material is rolled into a film, the thickness of the prepared dry film is uniform and the consistency is good, which solves the problems of holes or uneven edges on the electrode plate. The secondary battery prepared by this method improves the manufacturing efficiency and electrochemical performance of the battery.

[0046] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, and the lithium-ion battery includes the above-mentioned electrode plate.

[0047] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0048] Example 1

[0049] NCM622 is used as the positive electrode active material, SP is used as the conductive agent, polytetrafluoroethylene is used as the binder, and the mass ratio of the positive electrode active material, the conductive agent and the binder is 96:2:2. The positive electrode material and the conductive agent are added to the granulator according to the ratio.

[0050] Turn on the cooling water and mix at medium speed at 1300 rpm for 5 minutes;

[0051] Turn off the cooling water, run at 5800rpm, control the powder temperature at 95℃, take samples every 2 minutes to test the bulk density of the mixed material, and get the curve of the change of the bulk density of the mixed material over time. The results are shown in Figure 3 ;Depend on Figure 3 It can be seen that before 3 minutes, the bulk density of the material is relatively large, the material mixing uniformity and the degree of binder fiberization are average; from 3 minutes to 9 minutes, the material becomes fluffy and the binder fiberization effect is good; after 9 minutes, the flocculent material begins to break, and the fiberized binder begins to break due to the long mixing time, and the bulk density decreases, which is consistent with the bulk density of the positive active material NCM622 (1.15 g / cm 3 ), at this time, the binder is over-fiberized, and the resulting material is hard and difficult to press thin. Therefore, the material with good fiberization effect within the time period of 3min-9min was taken for scanning electron microscopy test, see Figure 4 .

[0052] Turn on the cooling water and stir at a low speed of 300rpm for 5 minutes. See the figure of powder after low-speed stirring. Figure 5 .

[0053] The fiberized electrode material was added to a vertical roller press and hot roller pressed at 120°C until the set thickness was formed into a dry positive electrode film. The cross-sectional SEM image of the prepared film is shown in Figure 6 The positive electrode film is laminated to both sides of the current collector by flat-plate hot pressing, and then the positive and negative electrodes are cut and laminated to obtain a secondary battery.

[0054] It can be seen from the above embodiments that in the processing of electrode materials, the powders are initially mixed by stirring at medium speed first, then stirred at high speed, and during the high-speed stirring, the change in bulk density is monitored to select fluffy and flocculent materials with good fiberization effect, and finally a low-speed breaking step is performed to prepare electrode materials with good mixing effect and uniform particle size, and then the electrode materials are used to prepare electrode films with uniform thickness, good consistency and good appearance performance.

[0055] Example 2

[0056] It is basically the same as Example 1, except that the conductive agent in the dry electrode powder fiberization processing method is graphene.

[0057] Example 3

[0058] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the powder temperature is controlled to be 120°C by high-speed mixing.

[0059] Example 4

[0060] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the powder temperature is controlled to be 150°C by high-speed mixing.

[0061] Example 5

[0062] It is basically the same as Example 1, except that the high-speed stirring speed is set to 5000 rpm in the dry electrode powder fiberization processing method.

[0063] Example 6

[0064] It is basically the same as Example 1, except that the high-speed stirring speed is set to 7000 rpm in the dry electrode powder fiberization processing method.

[0065] Example 7

[0066] It is basically the same as Example 1, except that the medium-speed stirring speed is set to 1000 rpm in the dry electrode powder fiberization processing method.

[0067] Example 8

[0068] It is basically the same as Example 1, except that the medium-speed stirring speed is set to 2000 rpm in the dry electrode powder fiberization processing method.

[0069] Example 9

[0070] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, medium-speed mixing is set to maintain the temperature at 25°C.

[0071] Example 10

[0072] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the medium-speed mixing is set to maintain the temperature at 50°C.

[0073] Embodiment 11

[0074] It is basically the same as Example 1, except that the low-speed stirring speed is set to 100 rpm in the dry electrode powder fiberization processing method.

[0075] Example 12

[0076] It is basically the same as Example 1, except that the low-speed stirring speed is set to 500 rpm in the dry electrode powder fiberization processing method.

[0077] Embodiment 13

[0078] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, a low-speed mixing is set to maintain the temperature at 25°C.

[0079] Embodiment 14

[0080] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the low-speed mixing is set to maintain the temperature at 35°C.

[0081] Comparative Example 1

[0082] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the positive electrode material and the conductive agent are not mixed at a medium speed first (that is, the positive electrode material, the conductive agent, and the binder are directly mixed at a high speed).

[0083] Comparative Example 2

[0084] It is basically the same as Example 1, except that the medium-speed stirring speed is set to 3000 rpm in the dry electrode powder fiberization processing method.

[0085] Comparative Example 3

[0086] It is basically the same as Example 1, except that the mixed material is not stirred at high speed in the dry electrode powder fiberization processing method.

[0087] Comparative Example 4

[0088] It is basically the same as Example 1, except that the high-speed stirring speed is set to 8000 rpm in the dry electrode powder fiberization processing method.

[0089] Comparative Example 5

[0090] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the fiberized mixed material is not dispersed at a low speed.

[0091] Comparative Example 6

[0092] It is basically the same as Example 1, except that the low-speed stirring speed is set to 1000 rpm in the dry electrode powder fiberization processing method.

[0093] Comparative Example 7

[0094] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the medium-speed mixing is set to maintain the temperature at 80°C.

[0095] Comparative Example 8

[0096] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the high-speed mixing holding temperature is set at 200°C.

[0097] Comparative Example 9

[0098] It is basically the same as Example 1, except that in the dry electrode powder fiberization processing method, the low-speed mixing is set to maintain the temperature at 60°C.

[0099] test:

[0100] 2. Test Method

[0101] 1. Bulk density test:

[0102] 1) Weigh the mass of the 250mL beaker and record it as M1.

[0103] 2) Fill the beaker with the sample to be tested and scrape off the excess sample on the beaker with a ruler. Avoid vibration during this process. Then weigh the total mass and record it as M2.

[0104] 3) Calculate the bulk density according to the following formula:

[0105] BD=(M2-M1) / V

[0106] Where:

[0107] BD-------The bulk density of the sample to be tested, unit: g / cm 3 ;

[0108] M1--------mass of beaker, unit: g;

[0109] M2--------Total mass of beaker and sample, unit: g;

[0110] V---------The volume of the beaker, unit: cm 3 .

[0111] 4) Repeat the measurement three times for one sample and take the arithmetic mean of the three measurement results as the bulk density value of the tested sample.

[0112] 2. Button cell first efficiency and gram capacity test:

[0113] The dry-process electrodes are assembled into button-type half-cells. The electrolyte is LiPF6 / EC+DEC+DMC (volume ratio of 1:1:1). The metal lithium sheet is the counter electrode. The diaphragm is made of polyethylene (PE), polypropylene (PP) or polyethylene propylene (PEP) composite film. The button-type battery is assembled in a glove box filled with argon.

[0114] Specific capacity and first effect test:

[0115] 1) Charge at a constant current of 0.1C until the termination voltage is reached, then switch to constant voltage charging until the charging current drops to 0.05C and stop charging. Let stand for 30 minutes;

[0116] 2) Discharge at a constant current of 0.1C until the end voltage is reached, then stand for 30 minutes and record the discharge specific capacity as the gram capacity of the dry electrode;

[0117] 3) The ratio of the first discharge capacity to the first charge capacity is taken as the first efficiency, and the charge and discharge cut-off voltage is 2.8-4.35 V. The test results are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] It can be seen from Table 1 above that the powders provided in the embodiment and the comparative example are respectively made into positive electrode sheets, and the dry positive electrode sheets are respectively assembled into button-type half-cells. The positive electrode sheets prepared by the electrode materials prepared in the embodiment of the present invention have good apparent performance of the membranes, and the initial efficiency and gram capacity of the obtained button-type half-cells are also very high. However, the membrane quality in the comparative example is poor, and even the membrane cannot be formed, and the performance of the corresponding battery is also poor. This is because: During the processing of the electrode material provided in the embodiment of the present invention, the following steps are followed: first stir at a medium speed to allow the raw materials to reach a preliminary mixed and uniform state, and then mix at a high speed, and during the high-speed mixing process, closely monitor the changes in the loose density, and when the loose density of the powder meets 20%<BD t When / BD0 is less than 50%, a material with good fiberization effect is obtained. After obtaining the above-mentioned material with good fiberization effect, the material is dispersed at a low speed to finally obtain an electrode material with good mixing effect and uniform particle size. Then, the electrode material is used to prepare a pole piece film with good electrochemical performance, and then the pole piece film is bonded to both sides of the current collector by flat-plate hot pressing, and then the positive and negative electrodes are cut and stacked respectively to obtain a secondary battery.

[0122] If the above steps are not followed during the processing of the electrode material or the temperature, time and speed during the stirring process change, the powder cannot reach the state required at each stage, and the prepared powder is unevenly mixed and has poor effect. When the electrode material is used for calendering film formation, the film quality is poor, or even film formation is impossible (such as Comparative Examples 3, 4 and 8), and the performance of the corresponding battery is also poor. Therefore, the solution provided by the embodiment of the present invention can be used to obtain an electrode material with good mixing effect and uniform particle size. When the electrode material is calendered into a film, the thickness of the prepared film is uniform and the consistency is good, which solves the problems of holes or uneven edges on the electrode film.

[0123] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for processing an electrode material, characterized in that: The following steps are involved: Step 1: Add the electrode active material and the conductive agent into a granulator, and stir at a medium speed of 1000-2000 rpm for 5-15 minutes, control the powder temperature to 25°C-50°C, obtain a uniform mixture, and test the bulk density of the mixture to be BD0; Step 2: Add the binder to the above mixture, and stir at a high speed of 5000-7000 rpm for 3-10 min. Control the powder temperature to 70°C-160°C to obtain a fiberized material. The bulk density BD of the fiberized material at a stirring time of t is required to be tested. t , among which, BD t <BD0, and 20%<BD t / BD0<50%; Step 3: The fibrous material is then dispersed at a low speed of 100-500 rpm for 5-10 min, and the powder temperature is controlled at 25° C.-35° C. to obtain an electrode material with uniform particles, wherein the particle size of the electrode material is 0.2-5 mm.

2. The processing method according to claim 1, characterized in that: The mass ratio of the electrode active material, the conductive agent and the binder is 80-98:1-5:1-10, wherein: The binder is a fiberizable binder, and the binder includes at least one of polyvinylidene fluoride, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber; The conductive agent comprises at least one of acetylene black, conductive carbon black, Ketjen black, graphene, carbon nanotubes and carbon fibers, and the bulk density of the conductive agent is 0.05-0.2 g / cm 3 ; The electrode active material is a positive electrode material or a negative electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium manganate, lithium cobaltate, lithium titanate and lithium nickel cobalt manganate. The bulk density of the positive electrode material is 1.0-2.0 g / cm 3 The negative electrode material includes at least one of graphite, silicon, silicon oxide, hard carbon and soft carbon, and the bulk density of the negative electrode material is 0.5-1.5g / cm 3 .

3. The processing method according to claim 1, characterized in that: In the step 2, the bulk density is tested by a Scott volumetric meter method or a vibrating funnel method.

4. The processing method according to claim 1, characterized in that: The granulator in the step one comprises: an outer cylinder, an inner cylinder sleeved in the outer cylinder and a cover arranged on the outer cylinder, a water flow channel is formed between the outer cylinder and the inner cylinder, a water inlet and a water outlet are arranged on the side wall of the outer cylinder, the water inlet and the water outlet are both communicated with the water flow channel, the water inlet is connected to a cooling water inlet pipe, the water outlet is connected to a cooling water outlet pipe, wherein the cooling water inlet pipe and the cooling water outlet pipe are both provided with control valves; a stirring shaft is arranged in the inner cylinder, and the stirring shaft is driven to rotate by a first rotary driver; a large paddle agitator and a small paddle agitator are sleeved on the stirring shaft, and the small paddle agitator and the large paddle agitator are arranged in sequence along the direction close to the bottom of the inner cylinder; a temperature probe is arranged in the inner cylinder, and the temperature probe is connected to a temperature display located outside the outer cylinder.

5. The processing method according to claim 4, characterized in that: The method for controlling the temperature of the powder in step one is: opening the control valve on the cooling water inlet pipe and the control valve on the cooling water outlet pipe, so that cooling water flows into the water flow channel; the method for controlling the temperature of the powder in step two is: closing the control valve on the cooling water inlet pipe, and keeping the control valve on the cooling water outlet pipe in an open state, so that there is no cooling water in the water flow channel; the method for controlling the temperature of the powder in step three is: opening the control valve on the cooling water inlet pipe, and keeping the control valve on the cooling water outlet pipe in an open state, so that cooling water flows into the water flow channel.

6. The processing method according to claim 4, characterized in that: The inner cylinder is driven to rotate by a second rotary driver, and the second rotary driver drives the inner cylinder to rotate in a direction opposite to the direction in which the first rotary driver drives the stirring shaft to rotate.

7. A method for processing an electrode plate, characterized in that: It includes: The electrode material is rolled into a dry film, the dry film is rolled up, and then the dry film is bonded to both sides of the current collector by flat-plate hot pressing to obtain a dry electrode sheet, wherein the electrode material is obtained by processing according to any one of claims 1-6.

8. A lithium ion battery, characterized in that: The lithium-ion battery comprises an electrode plate processed by the processing method according to claim 7.

Citation Information

Patent Citations

  • Dry method electrode plate preparation method, electrode plate prepared by adopting same and application of electrode plate

    CN112687833A

  • In-situ preparation method of dry-method electrode membrane and dry-method electrode thereof

    CN114171710A

  • Preparation method of dry electrode capable of continuously discharging

    CN114583111A

  • Method for monitoring fibrosis degree in dry-method membrane preparation process, dry-method membrane preparation method, and preparation method and application of dry-method electrode plate

    CN114441408A